Hilirisasi Komoditi Mineral: Studi Kasus Nikel di Indonesia - Chrissostomus Sitohang; Hanfritz Azis; Muhammad Syahdilani Hafiz (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Mineral downstreaming is a strategic policy designed to enhance the added value of mineral products and optimize the utilization of natural resources. This policy aims to reduce the export of raw ore and increase the production of finished goods domestically, which has significant potential to secure the country's foreign exchange reserves and strengthen Indonesia's competitiveness in the global market. This study aims to analyze the implications and effects of mineral downstreaming policies on Indonesia's economy. The methodology employed is a literature review using a descriptive qualitative approach. The findings indicate that by promoting further processing and innovation in technology development, nickel downstreaming not only yields positive economic impacts through increased revenue in the non-oil and gas sector and corporate contributions to state revenues but also significantly aids in maintaining environmental sustainability. The development of the nickel downstream industry not only creates new job opportunities and reduces unemployment rates but also stimulates growth in related industries while increasing the demand for domestic technology.